Developing safe and efficient CGBE editor based on Cas-embedding strategy - Tian Lin; Xin Wang; Yu Zhang; Guanglei Li; Xingxu Huang; Ming Shi (Synthetic and Systems Biotechnology)
CGBE (C-to-G base editor) systems, pivotal components within the base editing arsenal, enable the precise conversion of cytosines to guanines. However, conventional cytidine deaminases possess non-specific single-stranded DNA binding properties, leading to off-target effects and safety concerns. The Cas-embedding strategy, which involves embedding functional proteins like deaminases within the Cas9 enzyme's architecture, emerges as a method to mitigate these off-target effects. Our study pioneers the application of the Cas-embedding strategy to CGBE systems, engineering a suite of novel CGBE editors, CE-CGBE. The CE-CGBE that incorporated eA3A, RBMX and Udgx excelled in editing efficiency, editing purity, and indel formation was named HF-CGBE. HF-CGBE showed no significant difference in off-target effects compared to the negative control group for both DNA and RNA. In summary, the novel HF-CGBE editors we propose expand the base editing toolbox and provide therapeutic approaches for related pathogenic mutations.